IMPORTANT ASPECTS OF LEARNING AND TEACHING FOREIGN LANGUAGES - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
Our article systematically examines the phonetic, morphological, lexical, and syntactic levels of languages ​​and identifies their similarities and differences as well as their reasons. Today in our country, special attention is paid to measures to further develop the Uzbek language and improve language policy. Fortunately, not only native speakers but also foreign researchers are trying to learn the Uzbek language. Linguistic typology attempts to find structural laws of features in languages, while linguistic universals examine how these features are distributed in the languages ​​of the world. It is also possible to study languages ​​for theoretical purposes.